Neglected Retained Suprapubic Catheter with Varied Management Options: A Case Series - Gite, Venkat A; Sharma, Shashank; Agrawal, Mayank; Shaw, Vivek (Journal of Society of Surgeons of Nepal, 2021)
Supra-pubic catheterization of bladder is used as a short or long term alternative to per-urethtral catheterization.Some catheter materials are more resistant to encrustation than others. If kept indwelling for longer duration, sooner or later all catheters cause complications like urinary tract infection (UTI), trauma, peri-catheter leakage, non-deflation of balloon, encrustations and stone formations resulting into retained catheter.Stone formation over neglected indwelling catheter is not an unusual clinical scenario and its management depends on etiology of catheter retention and complication.This article discusses etiopathogenesis, clinical presentations, diagnosis and varied management options used for the neglected retained supra-pubic catheter in three cases